New Frontiers in Comparative Victimology: Introduction to the Special Issue of the International Journal of Offender Therapy and Comparative Criminology - Posick, Chad (International journal of offender therapy and comparative criminology, 2024)
This special issue of the International Journal of Offender Therapy and Comparative Criminology intends to expand the examination of victimology and victim issues. The social problem of violence is universal, and there is much to learn from policies and programs that are found to be effective across the globe. The four issues in this special issue span global problems such as cybercrime, interpersonal violence, violent socialization, and the victimization of college students. Solutions to these harms include micro-level programmatic efforts as well as broader social-political efforts.